In situ hybridization studies of prostacyclin receptor mRNA expression in various mouse organs. - Oida, H. (1995)
1. Expression of prostacyclin receptor (IP receptor) mRNA was examined in various mouse organs, and the cells expressing IP receptor mRNA were identified by in situ hybridization studies. Co-localization of mRNA for the IP receptor with that for preprotachykinin A (PPTA), a precursor protein for substance P, with mRNA for the prostaglandin E receptor subtypes (EP1, EP3 and EP4), and with renin mRNA, was examined by double in situ hybridization studies in the dorsal root ganglion and kidney, respectively. 2. IP receptor mRNA was expressed in the thymus and spleen. Expression in the thymus was found exclusively in the medulla, where mature thymocytes expressed transcripts for the IP receptor. Expression in the spleen was found as scattered signals over the white pulp and as punctate signals in the red pulp. The former was found in splenic lymphocytes and the latter in megakaryocytes. 3. IP receptor mRNA was also expressed in the vascular tissues of various organs such as the aorta, coronary arteries, pulmonary arteries and the cerebral arteries, where its expression was confined to smooth muscle cells. No expression was found in veins. In the kidney, IP receptor mRNA was detected in the interlobular arteries and glomerular arterioles but not in the juxtaglomerular (JG) cells which were labelled with the renin mRNA probe. 4. IP receptor mRNA was expressed in about 40% of the neurones in the dorsal root ganglion. Both small- and large-sized neurones were labelled but no labelling was found in the glia. Expression of PPTA mRNA was found in about 30% of total neurones. About 70% of these neurones expressed IP receptor mRNA, and about half of the IP receptor-positive neurones expressed PPTA mRNA. In addition to IP mRNA, mRNAs for EP1, EP3 and EP4 receptors were expressed in about 30%, 50% and 20%, respectively, of the dorsal root ganglion neurones. About 25%, 41% and 24% of the IP receptor-positive neurons co-expressed the EP1, EP3 and EP4 receptor, respectively. 5. These results not only verified IP receptor expression in various cells and tissues known to be sensitive to prostacyclin, but also revealed its expression in other systems, which urges the study of the actions of prostacyclin in these tissues. They also indicated that the actions of prostacyclin on blood vessels and platelets are mediated by the same type of receptor. Absence of IP receptor mRNA in the JG cells suggests that the action of prostacyclin on renin release may be indirect.